C-reactive Protein Elevation Is Associated With QTc Interval Prolongation in Patients Hospitalized With COVID-19 - Isakadze, Nino; Engels, Marc C.; Beer, Dominik; McClellan, Rebecca; Yanek, Lisa R.; Mondaloo, Bahareh; Hays, Allison G.; Metkus, Thomas S.; Calkins, Hugh; Barth, Andreas S. (Frontiers in Cardiovascular Medicine, 2022)
Objective: To assess the effect of marked interval changes in the inflammatory marker C- reactive protein (CRP) on QTc interval in patients hospitalized with COVID- 19. Methods: In this retrospective cohort study of hospitalized adult patients admitted with COVID- 19 infection, we identified 85 patients who had markedly elevated CRP levels and serial measurements of an electrocardiogram (ECG) and CRP during the same admission. We compared mean QTc interval duration, and other clinical and ECG characteristics between times when CRP values were high and low. We performed mixed effects linear regression analysis to identify associations between CRP levels and QTc interval in univariable and adjusted models. Results: Mean age was 58±16 years; 39% were women; 41% were Black, 25% White. On average, the QTc interval calculated via the Bazett formula was 15 ms higher when the CRP values were “high” vs “low” (447 ms (IQR 427 – 472 ms) and 432 ms (IQR 412 – 452 ms), respectively). A 10 mg/L increase in CRP was associated with a 1.5 ms increase in QTc interval (β coefficient 0.15, 95% CI (0.06 – 0.24). In a fully adjusted model for sociodemographic, ECG and clinical factors, the association remained significant (β coefficient 0.14, 95% CI 0.05 – 0.23). Conclusion: An interval QTc interval prolongation is observed with a marked elevation in CRP levels in COVID-19 patients.